2021
DOI: 10.1177/10870547211017982
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Physical Activity for Children with Attention Deficit Hyperactivity Disorder: A Meta-Analysis of Randomized Controlled Trials

Abstract: Background: This systematic review and meta-analysis assesses the efficacy of regular, moderate to vigorous physical activity (MVPA) for attention deficit hyperactivity disorder (ADHD) in children and adolescents in randomized controlled trials (RCTs). Methods: RCTs including children and adolescents with clinically diagnosed ADHD, implementing regular MVPA, and assessing ADHD core-symptoms on a valid rating scale post-intervention (primary outcome) were included. Outcomes were pooled through random-effects me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 85 publications
1
25
0
1
Order By: Relevance
“…Since the therapeutic efficacy of PEs is rather moderate, PEs are mostly suggested as a supplementary treatment ( Seiffer et al, 2022 ). At the same time, action of PEs appears as an experimental paradigm to study interlacement between autophagy and neuroplasticity in the context of a search for pro-cognitive therapy.…”
Section: Physical Exercises As An Alternative To the "Easy Come-easy ...mentioning
confidence: 99%
“…Since the therapeutic efficacy of PEs is rather moderate, PEs are mostly suggested as a supplementary treatment ( Seiffer et al, 2022 ). At the same time, action of PEs appears as an experimental paradigm to study interlacement between autophagy and neuroplasticity in the context of a search for pro-cognitive therapy.…”
Section: Physical Exercises As An Alternative To the "Easy Come-easy ...mentioning
confidence: 99%
“…Physical exercise was found to have the greatest mean effect size, particularly for inhibition ( Lambez et al, 2020 ). Seiffer et al (2022) studied the efficacy of moderate to vigorous exercise (MVPA) on children with attention deficit hyperactivity disorder (ADHD), focusing on the intensity component of physical activity. The study indicated that MVPA was the most effective treatment for ADHD and that it might be used as an alternative ( Seiffer et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results of another systematic review showed positive effects of a 1-h long PA and short duration activities on attention as well as on-task behaviors (Ruhland and Lange, 2021 ). However, when Seiffer et al investigated the efficacy of PA on children with ADHD, they observed that moderate-to-vigorous PA (MVPA) had only a small effect on total ADHD core symptoms (Seiffer et al, 2021 ). Another study also found that there were only small improvements in inhibitory control when PA was combined with cognitive training patterns (Dhir et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reviews and meta-analyses typically face some limitations, such as a small number of studies (Biddle et al, 2019 ; Schuch et al, 2019 ; Andermo et al, 2020 ; Lambez et al, 2020 ; Carter et al, 2021 ; Liang et al, 2021 ), differences in methodologies (Lambez et al, 2020 ; Vysniauske et al, 2020 ; Dhir et al, 2021 ; Seiffer et al, 2021 ), differences between studies in assessing PA and mental health outcomes (Biddle et al, 2019 ; Andermo et al, 2020 ; Liang et al, 2021 ; Ruhland and Lange, 2021 ; Welsch et al, 2021 ), studies with low or moderate quality and high risk of bias (Rodriguez-Ayllon et al, 2019 ; Vysniauske et al, 2020 ; Carter et al, 2021 ; Dhir et al, 2021 ; Seiffer et al, 2021 ; Welsch et al, 2021 ), and non-representative samples (Biddle et al, 2019 ; Rodriguez-Ayllon et al, 2019 ; Vysniauske et al, 2020 ; Bourke et al, 2021 ; Liang et al, 2021 ; Welsch et al, 2021 ). Individual studies have small and non-representative samples (Ahn et al, 2018 ; Bowe et al, 2021 ; Mercurio et al, 2021 ), low quality, no long-term follow-ups, and inadequate consideration of real-world implementation factors for intervention studies (Parker et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%